Isolasi Yeast Inulinolitik dan Optimasi Produksi Inulinase Pada Berbagai Konsentrasi Nitrogen Yeast Ekstrak Sebagai Sumber N - Wijanarka, Wijanarka -; Sutariningsih, Endang; Dewi, Kumala -; Indrianto, Ari - (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2011)
Inulin is a linier fructose polymer of plant origin found in the Jerusalem artichoke, dandelion, dahlia tuber and several other members of the family Compositae. Inulin is one of the numerous polysaccharides of plant origin that contain glukose or fructose and that can be used in the food industry and in industrial fermentations as a subtrate. Fifteen yeast growing on inulin as the sole carbon and energi source. An inulinase activity in the liquid culture was measured with sugar reduction. The best optimization conditinos at concentration of 0.75% inulin and 12 hour incubation time. On condition that the optimization of inulin activity produced 0.8772 IU by isolate P 12. These yeast have potential uses in the preparation of ingredient food prebiotic.